Liquid-Supported Dentures: A Soft Option-A Case Report - Anoop Jain; Shivakumar Puranik; M. S. Jagadeesh; Puttaraj Kattimani; Savita Akki; Pawan Kumar; Vijaya laxmi' (Hindawi Limited, 2013)
Liquid-supported denture technique allows continued adaptation of denture to the mucosa both at resting and functional state. A complete denture prosthesis is unacceptable if it violates the foundation on which it rests. In this case, a technique for fabrication of a complete denture prosthesis that eliminates the disadvantages of tissue conditioners and soft liners (i.e., poor bond strength to acrylic, candidal colonization, etc.) and preserves the remaining tissues is described. Liquid-supported denture can be a permanent solution to some patients with problematic conditions like diabetes, xerostomia, atrophied ridge, and so forth.